MANAJEMEN PERPUSTAKAAN SEBAGAI UPAYA MENINGKATKAN MINAT BACA (STUDI DI SD NEGERI 1 BLIMBING KARANGNONGKO KLATEN) - Dwi Irmawati; Syamsul Bakri (Juremi: Jurnal Riset Ekonomi, 2022)
Library very important in educational environment.Library functions and the role of very great in education.Facilities sufficient very helpful a growing a students to make reading interest are.People schools teachers and students are compulsory to get information through reading. This research aims to improve student reading interest in primary schools n 1 blimbing.In the research uses a qualitative methodology where this method is use case studies.The information from the primary data that is the school and the head librarian.Secondary data in form of data report or documentary.Data collection techniques used by interviews with, the observations of the field as well as. documentation. Research indicate that implementation of library management primary school n 1 blimbing can be seen from planning, organizing, actuating library and supervision have good enough.Obstacles ketenagaan who experienced the lack of primary school librarian in the library n 1 blimbing